The lipid‐binding START domain regulates the dimerization of ATML1 via modulating the ZIP motif activity in Arabidopsis thaliana. (10th October 2021) - Nagata, Kenji; Abe, Mitsutomo
Abstract: In Arabidopsis thaliana, the epidermis is the outermost cell layer composed of many specialized types of epidermal cells, such as pavement cells, trichomes, and guard cells. The homeodomain‐leucine zipper (HD‐ZIP) class Ⅳ transcription factors (TFs), which are unique to the plant kingdom, have been recognized as key regulators of epidermis development. Unlike animal HD proteins, which can bind to DNA as monomers, plant HD‐ZIP class Ⅳ TFs bind to DNA as dimers, although little is known about the regulation of their dimerization process. Here, we show that the homodimerization of ARABIDOPSIS THALIANA MERISTEM LAYER 1 (ATML1) — HD‐ZIP class Ⅳ TF that is required for protoderm development — is regulated by the lipid‐binding steroidogenic acute regulatory protein‐related lipid transfer (START) domain. We found that ATML1 forms homodimer through interaction via its ZIP motif in yeast and plant cells, although the interaction is abolished by generating a mutation into the lipid‐binding START domain to disrupt the lipid‐binding ability. These results suggest that lipidic ligands function as key regulators of protoderm development via modulating the dimerization of ATML1. Abstract : The START domain regulates the homodimerization of ATML1 via modulating ZIP motif activity in a VLCFA‐Cer‐dependent manner, restricting the activity of ATML1 to the outermost cells.